Intraoperative Pathologic Consultation on Hysterectomy Specimens for Endometrial Cancer: An Assessment of the Accuracy of Frozen Sections, "Gross-Only" Evaluations, and Obtaining Random Sections of a Grossly "Normal" Endometrium. Issue 4 (9th September 2017) - Desouki, Mohamed Mokhtar; Li, Zaibo; Hameed, Omar; Fadare, Oluwole
Abstract: Objectives: Pathologic intraoperative consultation (IOC) is a common approach for segregating the subset of patients with endometrial cancer who likely require a lymphadenectomy. Methods: We evaluate factors related to the performance and value of IOC, including the accuracy of frozen sections, "gross-only examinations, " and obtaining random sections when a gross lesion is not apparent. Results: IOC was performed by gross examination only in 17 (8%) of 250 cases, the specificity and negative predictive value of which in diagnosing cancer were 100% and 85%, respectively. Among the 64 cases wherein a gross lesion was not apparent and random sections were examined, a final diagnosis of carcinoma was rendered in 20, of which only three (15%) had a diagnosable malignancy on the random section. The frozen-section/final diagnosis concordance was 80% for tumor grade. Determining the depth of myometrial invasion was problematic, with 36% underestimation and 2.6% overestimation. Conclusions: Obtaining random sections in the absence of a gross lesion has no significant benefit, and a negative result is likely to provide inaccurate data to the surgeon. Frozen-section analyses are a generally reliable tool to determine "low-risk" pathologic parameters that were evaluated herein when a gross lesion is present.